Transformative Strategies: Digital Marketing’s Impact on the Manufacturing Sector’s Competitive Edge - Firdaus, Mochamad Daffa Esta; Manafe, Leonard Adrie; Wulansari, Christina (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze how Solid Engineering SUMAS, a company that manufactures solid doors, implements digital marketing strategies and to assess how effective those measures are in enhancing brand strength and sales. The researcher adopts a qualitative approach with a case study method to directly experience the challenges and successes faced by the company when implementing internet-based marketing. Data was collected through in-depth interviews with five key informants, supplemented by participatory observation and an examination of internal documents. The results of the analysis show that the utilization of social media, search engine optimization, and various other digital platforms has succeeded in elevating product visibility while also expanding the market reach. Nevertheless, the company still struggles with consistency in content creation and relevance in managing its advertising budget. Furthermore, this study finds the need to strengthen SEO strategies and utilize analytics data to enhance the effectiveness of digital marketing sustainably. Based on these findings, this research proposes recommendations regarding the development of more creative content, exploration of new digital platforms, and investment in human resources and analytic tools for better long-term results. Thus, this study is expected to provide useful insights for other manufacturing companies that are designing and refining their digital marketing tactics.